Perencanaan Pembelajaran Matematika Kurikulum Berbasis Cinta pada SMK Kesehatan Athallah - Ahmawati, Fitri Dewi; Zainuri, Ahmad; Arni, Arni (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to describe and analyze the planning of mathematics learning based on a love-centered curriculum at Athalla Health Vocational School. The curriculum was developed in response to the low motivation and academic achievement of nursing and midwifery students, who often perceive mathematics as irrelevant to their future professions. The love-based curriculum emphasizes the integration of compassion, empathy, and care values into the teaching process to create a more supportive, enjoyable, and meaningful learning environment. This study employs a qualitative method with a case study approach, collecting data through in-depth interviews with teachers and students, classroom observations, and analysis of lesson planning documents. Through the implementation of a love-centered curriculum, it is expected that students’ motivation, conceptual understanding, and learning outcomes will improve. Furthermore, this research aims to demonstrate how mathematics learning integrated with humanitarian values can foster positive character traits such as empathy, responsibility, and collaboration, which are essential qualities for future health professionals.